Respuesta :

Answer:

Nine: 5, 7, 9, 11

Ten: 13, 17, 21, 25

Step-by-step explanation:

Nine

f(n) = 2n + 3

f(1) = 2*1 + 3       Substitute 1 for n

f(1) = 2 + 3          Multiply 2 * 1

f(1) = 5                Add 3

f(2) = 2n + 3       Substitute 2 for n

f(2) = 2*2 + 3     Combine the factors

f(2) = 4 + 3         Add the terms

f(2) = 7

f(3) = 9                Answer

f(4) = 11               Answer

Ten

f(n) = 4n + 9

f(1) = 4*1 + 9       Substitute 1 for n

f(1) = 4 + 9         Combine the factors

f(1) = 13              Add the terms

f(2) = 4*2 + 9     Substitute 2 for n

f(2) = 8 + 9         The factors (2 and 4) have been combined

f(2) = 17               Add 9

f(3) = 21               Answer

f(4) = 25              Answer

ACCESS MORE